Myodes glareolus - Don E. Wilson; Russell A. Mittermeier; Thomas E. Lacher, Jr (Lynx Edicions, 2017)
49. Bank Vole Mpyodes glareolus French: Campagnol rousséatre / German: Rotelmaus / Spanish: Topillo rojo Taxonomy. Mus glareolus Schreber, 1780, Island of Lolland, Denmark. Throughout the 20" century, glareolus was included in FEvotomys or Clethrionomys; both generic names are junior synonyms of Myodes. Myodes glareolus is more closely related to M. centralis and M. macrotis than to M. rutilus. Past and present hybridization with M. rutilus was documented in the zone of sympatry, and all individuals with alien mitochondrial genome are M. glareolus. Large number of subspecific names was proposed for M. glareolus, but they were never revised. Some sources list 26 subspecies in western Europe alone, while others recognized 10-13 subspecies from the entire distribution. Phylogeographic studies using molecular markers retrieved complex evolutionary history and survival in multiple glacial refugia. Monotypic. Distribution. W Europe from Atlantic coast E to Yenisei River, N border set by Arctic tundra and S border frequently coincides with mountain ranges: Pyrenees, Alps, Apennines, and Balkan in S Europe, Pontic Mts in Anatolia, and Altai and Sayan Mts in C Asia; widespread on islands offshore Atlantic and Baltic coasts. Introduced to SW Ireland. Descriptive notes. Head-body 80-135 mm, tail 32-72 mm; weight 12-61 g. Sexes of Bank Voles are similarly sized. Size varies geographically and seasonally. They tend to be small in central and eastern parts of the distribution, and they are large in European mountains and northern European Russia and on some islands off Great Britain. The Bank Vole is slender, with large semicircular ears and relatively long tail ¢.50% of head-body length. Females have four pairs of nipples, and there are six plantar pads. Pelage is soft, and denser in winter (204 hairs/mm?) than summer (134 hairs/ mm?). Back is rusty, flanks are gray, and belly is light gray, occasionally washed buff. Contrast between back and flank pelage is obvious, particularly in adults. Juveniles are darker and less ...